THE USE OF CLUSTERING TECHNIQUE TO IMPROVE STUDENTS’ SKILL IN WRITING DESCRIPTIVE TEXT - Della Hanafiawi; Harry Muharam; Aseptiana Parmawati (PROJECT (Professional Journal of English Education), 2020)
Students have to learn the four basic language skill, they are listening, reading, writing, speaking. One of the most important skill that is Writing. It can make students to share the ideas into written form in the text or paragraph with the right order of generic structure. The purpose of this research was to find out the improving of students writing skill  of descriptive text using clustering technique at seventh grade students of SMPN 11 Cimahi in the Academic Year of 2018 – 2019. This research used Classroom Action Research. The research was carried out in  two cycles and each cycle consisted of four steps, they are Planning, Action, Observation, and Reflection. Most of the students gradually gained good scores at the end of each  cycles. The students responses showed that they interested to learn writing.The score of Minimum Mastery Criterion of English lesson was 75. The Students mean score of pretest 45,7. The mean score in postest 1 was 53,7. The mean score of posttest 2 was 79,3. From this result, the researcher concludes that teaching descriptive text using clustering technique can improve their writing ability and the atmosphere of the class was more alive. Keywords:  CAR, Writing Skill